Product intervention for retail structured investment products: A comparison of rules in Singapore, Hong Kong and Taiwan - CHEN, Christopher C. H. (Institutional Knowledge at Singapore Management University, 2016)
This article compares new product intervention rules in Singapore, Hong Kong and Taiwan for complex structured investment products. Singapore’s approach is to improve firms’ internal safeguard, while Hong Kong’s approach is to require prior authorisation for new unlisted structured investment products by the securities regulator. Taiwan’s approach is to have a self regulatory body reviewing a product beforehand. This article argues that it is difficult to review the merit of a financial product in advance and thus it is difficult to have a true gatekeeper for toxic financial products. Before product intervention, we must first identify clear objectives. Regulators have to strengthen the accountability of the reviewer and create concrete review standards if additional ex ante product review is preferred. Regulators may also consider setting up some minimum standards for retail financial products through public debate in order to filter unwanted features from the retail market.